Uncontrolled batch culture of scenedesmus - Wong, Jing Jing (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Biodiesel is an alternative to the fossil fuels. The microalgae are potentially used as non-food feedstock for biodiesel production because they have fast growth rate, sustainable in non-arable land, and high lipid content. The objective of this study is to determine feasibility of sago effluent as culture medium to grow Scenedesmus dimorphus for biomass and lipid production. In this project, S. dimorphus was grown in Proteose medium (control), filtered sago effluent (FSE), and filtered pond water (FPW) amended with 20 g/L NaHCO3.The biomass was harvested after 20 days using polyglutamic acid flocculation method aided by centrifugation. Then, lipid was extracted from the dried biomass using Soxhlet extraction method. After 20 days cultivation, it was found that the biomass of S. dimorphus grown in stirred Proteose medium, FSE and FPW (amended with NaHCO3) increased by 36.17%, 102.27%, and 106.45%, respectively. The lipid was 6.88%, 6.17%, and 5.94%, respectively. The results showed that FSE can be potentially utilized as the culture medium to grow S. dimorphus for biomass and lipid production. Although the increased of biomass in FSE was much higher (over 100%) compared to the standard medium (Proteose, 36%), the amount of lipid among the three tested was low and almost similar, at about 6%.